การลดทอนคลื่นของแผ่นดินไหวระยะไกลในประเทศไทย - พิธาน ไพโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To propose the simple attenuation relations for peak period, peak ground distance (PGD), peak ground velocity (PGV) and peak ground acceleration (PGA) of various far field earthquakes recorded by the seismometers installed around Thailand. There are currently 29 seismic stations being active as earthquakes recorded station in Thailand. The main sources of far field earthquakes arrived are from three areas namely the regions around Sumatra, Myanmar and Andaman Sea. The epicenter distances varied from 300 to 3,000 kilometers. The total of 72 earthquakes recorded during 2006 to 2008 were used in formulation of the proposed correlations. The proposed correlations were divided according to the mentioned earthquake source zones. It was found that peak period was increased by distance from epicenters but peak ground distance, peak ground velocity and peak ground acceleration were attenuated by distance from epicenters. The proposed correlations for each earthquake sources were further subdivided according to the magnitudes of the events.